INTERVIEW WITH DR. ELÍAS CAPRILES ARIAS DURING HIS VISIT AS A GUEST PROFESSOR AT THE DEPARTMENT OF PHILOSOPHY OF THE UNIVERSIDAD NACIONAL. - Hernádez Castro, Esteban Alonso (2007)
In the month of June, the Department of Philosophy of the Universidad Nacional in Costa Rica, in coordination with the project Pensamos Dialogando, was pleased to receive the visit from Dr. Elías Capriles Arias, who carried out a series of academic activities, in which he presented some of the most important topics of his long trajectory as an academic and practicing instructor of Santi Maha Sangha at the community Dzogchen. Here is a brief interview about some of his recent work titled Alienación, crisis ecológico- económica y regeneración. Esencia, desarrollo y modos de producción de la alienación, y erradicación de esta en el ecomunismo decrecentista y libertario (Universidad de Los Andes, 2012).